THE EFFECT OF USING ANAGRAM GAME ON STUDENTS’ VOCABULARY MASTERY (A STUDY AT THE ELEVENTH GRADE OF SMA HARAPAN PADANGSIDIMPUAN 2020 – 2021 ACADEMIC YEAR) - EDO ZERRISON SIHOMBING (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The objective of this research are to know: 1) The application of anagram game in teaching vocabulary mastery, 2) The students’ vocabulary mastery before and after using anagram game, 3) Whether there is a significant effect of anagram game on students’ vocabulary mastery at the eleventh grade students of SMA HarapanPadangsidimpuan. This research uses experimental method with pre-experimental research design; one group pretest-posttest design. The population is all of the eleventh grade students which consist of 104 students and the samples are 31 students gotten by using systematic sampling.In collecting the data, the researcher uses observation sheet to get the data of the application of anagram game and test to get the data of the students’ vocabulary mastery. The result of the application of anagram gameis3.5, it is categorized “very good”. The mean score of the students’ vocabulary masteryis40.09, it is categorized “fail”. Meanwhile after using anagram game was 63.11, it is categorized “enough”. The researcher uses statistic process in analyzing the data by using ttestformula. Based on the data that has been analyzed, the result of data analyzing showed that ttest is higher than ttable (ttest3.75>ttable 2.04). So, the hypothesis is accepted. It means that there is a significant effect of using anagram game on students’ vocabulary mastery at the eleventh grade students of SMA HarapanPadangsidimpuan in 2020/2021 Academic Year. Keywords:anagram game, vocabulary.